Unified description of early universe in scalar-tensor theory - Singh C.P.; Ram S. (My University, 2025)
A spatially homogeneous and isotropic Robertson-Walker model with zero-curvature of the universe is studied in Saez-Ballester scalar-tensor theory. Exact solutions of the field equations are obtained for two different early phases of the universe viz. the inflationary and the radiation-dominated phases by using gamma-law equation of state p = (γ - 1)ρ in the presence of perfect fluid. The γ-index describing the material content varies continuously with cosmic time so that in the course of its evolution, the universe goes through a transition from an inflationary phase to a radiation-dominated phase. The coupling parameter ω is allowed to depend on the cosmic time. The nature of scalar field and other physical significance have also been discussed.